CD44 Acts as a Signaling Platform Controlling Tumor Progression and Metastasis - Orian-Rousseau, Véronique (Frontiers in Immunology, 2015)
CD44 proteins emerge as major signal transduction controller. CD44 isoforms participate in several signalling pathways ranging from growth factor-induced signalling to Wnt-regulated pathways. The role of CD44 in tumour progression and metastasis is most likely linked to its function as a signalling hub. More and more evidence suggests as well that CD44 is not only a mere cancer stem cell marker but is directly involved in tumour and metastasis initiation. It is foreseeable that a link between the expression of CD44 on cancer stem cells and its function as a regulator of cell signalling will be drawn in a near future.